Teacher Performance Model: Information Technology, Organizational Culture, Motivation Facilities and Infrastructure - Selvi Yona Sari; Prima Sari Pascariati Kasman; Desi Permata Sari; Hapzi Ali (EDUTEC : Journal of Education And Technology, 2022)
This study aims to find out the models that influence teacher performance, namely: information technology, organizational culture, motivation, as well as facilities and infrastructure . Data collection methods to be used in the study is the collection of data by conducting a review on the company to getthe image n needed by conducting interviews, while the results of this study are teknologi information affects positive and significant on performance; organizational culture has a positive and significant effect on performance; motivation has a positive and significant effect on performance ; Facilities and infrastructure have a positive and significant effect on performance.